2011
DOI: 10.1111/j.1365-2915.2011.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat shock proteins and subolesin affects stress responses,Anaplasma phagocytophiluminfection and questing behaviour in the tick,Ixodes scapularis

Abstract: We characterized the effects of subolesin and heat shock protein (HSP) expression on Ixodes scapularis Say (Acari: Ixodidae) stress responses to heat shock and feeding, questing behaviour and Anaplasma phagocytophilum (Rickettsiales: Anaplasmataceae) infection. Ticks and cultured tick cells were analysed before and after subolesin, hsp20 and hsp70 gene knock-down by RNA interference. The results of these studies confirm that HSPs are involved in the tick cell response to heat stress and that subolesin and HSPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 55 publications
3
71
0
Order By: Relevance
“…Subolesin expression is induced in response to pathogen infection in ticks and plays an important role in the tick immune response to pathogen infection through the regulation of genes involved in innate immunity (14,16,56,59). As in previous experiments, subolesin mRNA levels did not change in response to A. phagocytophilum infection of ISE6 tick cells but increased in tick guts and salivary glands (12,60). However, subolesin protein levels increased in A. phagocytophilum-infected ISE6 tick cells, suggesting that posttranscriptional mechanisms affect subolesin levels in response to infection (21,61).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Subolesin expression is induced in response to pathogen infection in ticks and plays an important role in the tick immune response to pathogen infection through the regulation of genes involved in innate immunity (14,16,56,59). As in previous experiments, subolesin mRNA levels did not change in response to A. phagocytophilum infection of ISE6 tick cells but increased in tick guts and salivary glands (12,60). However, subolesin protein levels increased in A. phagocytophilum-infected ISE6 tick cells, suggesting that posttranscriptional mechanisms affect subolesin levels in response to infection (21,61).…”
Section: Discussionsupporting
confidence: 60%
“…Subolesin knockdown resulted in higher A. phagocytophilum infection levels in ISE6 tick cells, supporting its role in the tick immune response. However, in tick guts and salivary glands, subolesin knockdown did not affect pathogen infection levels, probably due to the role of subolesin in tissue structure and development, which are required for pathogen infection (16,25,62), pointing to differences between in vitro and in vivo studies (12,21,60).…”
Section: Discussionmentioning
confidence: 99%
“…In the study reported here, Hsp70 and Hsp90 were overrepresented in infected tick cells. The increase in Hsp levels counteracts the negative effect of heat shock and pathogen infection on tick questing behavior and increases tick survival, those playing an important role in pathogen transmission and the adaptation of tick populations to challenging environmental conditions (70,71). These results also highlight coevolutionary mechanisms by which ticks benefit from A. phagocytophilum infection by increasing survival while pathogens guarantee transmission to susceptible hosts.…”
Section: Discussionmentioning
confidence: 73%
“…Recent results have shown how ticks benefit from infection by A. phagocytophilum (69,70). Neelakanta et al (69) demonstrated that infection with A. phagocytophilum induces I. scapularis ticks to express an antifreeze glycoprotein that increases tick cold tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The heat shock response is a conserved reaction of both cells and organisms to high temperatures and other stress conditions, and is effected by HSPs [41]. It has been reported that HSP20 can protect tick cells from stress, impact tick behavior such as questing speed, and can be involved in the I. scapularis protective response to A. phagocytophilum infection [42], [43]. However, these studies also reported that in the natural vector-pathogen relationship, HSPs and other stress response proteins were not strongly activated, which is likely due to tick-pathogen co-evolution [43].…”
Section: Heat Shock Proteins (Hsp) Familymentioning
confidence: 99%